THE ROLE OF TEACHER AND PARENTS IN LEARNING ONLINE IN SCIENCE COURSES AT SD NEGERI - Firda Ayu Cahyaning Dewi; Karma Iswasta Eka (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
This research was conducted to find out the role played by parents and teachers in online learning activities at SD Negeri Cibentang 02, Bantarkawung District during the pandemic and the obstacles parents and teachers had in implementing online learning. The research was a descriptive qualitative study, in class V SD Negeri Cibentang 02 Bantarkawung District and the informants in this study were eight parents of class V and teachers of class V. The data collection techniques used in this study were interviews, observation and documentation. Data obtained from informants were then analyzed by triangulation of sources, triangulation of techniques and research results. The results of the research that has been conducted on the role of parents and teachers in online learning of science subjects, show that parents provide direction and assistance to children, provide facilities to support learning activities and motivate and advise children to learn. The role of the teacher in the teacher's online learning activities is as a mediator, motivator, informator of learning organizers. Obstacles experienced by parents when providing assistance to children, namely time constraints due to parents' lack of mastery of children's learning material by parents and the condition of students who still like to play. The inhibiting factors experienced by teachers include poor network and facilities because not all students have androids and quotas to take part in online learning activities. Factors supporting the role of teachers and parents in online learning include student activity when learning, smooth and stable internet network, creative and innovative learning media.